2009
DOI: 10.1002/pmic.200800394
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional proteome reference maps for the human pathogenic filamentous fungus Aspergillus fumigatus

Abstract: The filamentous fungus Aspergillus fumigatus has become the most important airborne fungal pathogen causing life-threatening infections in immunosuppressed patients. We established a 2-D reference map for A. fumigatus. Using MALDI-TOF-MS/MS, we identified 381 spots representing 334 proteins. Proteins involved in cellular metabolism, protein synthesis, transport processes and cell cycle were most abundant. Furthermore, we established a protocol for the isolation of mitochondria of A. fumigatus and developed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
87
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 38 publications
(42 reference statements)
7
87
1
Order By: Relevance
“…Interestingly, two other "immunogenic" proteins, the enolase Aspf22 and Shm2, were detected in immunoblots using sera from patients with allergic bronchopulmonary aspergillosis (50). In addition, Shm2 belongs to one of the most abundant proteins identified in the mycelial proteome (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, two other "immunogenic" proteins, the enolase Aspf22 and Shm2, were detected in immunoblots using sera from patients with allergic bronchopulmonary aspergillosis (50). In addition, Shm2 belongs to one of the most abundant proteins identified in the mycelial proteome (21).…”
Section: Discussionmentioning
confidence: 99%
“…The initially inhaled resting conidia (RC) convert to swollen conidia (SC) within 4-5 h upon arrival in the lungs and germinate to form germ tubes and, later, hyphae (18). Proteomic approaches revealed differences in the most abundant proteins present in conidia and hyphae (19)(20)(21). Therefore, further variability in potential T cell Ags may result from the morphogenic status of the fungus at the time of encounter with the immune system, which might significantly impact the generation of a specific T cell response.…”
mentioning
confidence: 99%
“…To overcome these limitations, a cell fractionation approach can be used to better resolve total proteins (43). Furthermore, to obtain larger numbers of identified proteins and provide more in-depth analysis, a non-gel-based system of isobaric tagging for relative and absolute quantitation (iTRAQ) is now available.…”
mentioning
confidence: 99%
“…Recently, novel biomarkers that can be used as drug targets or markers of effective treatment have been identified by microarray genomic analysis or other methods of RNA analysis (10,37,40). Proteomic analysis relying on two-dimensional (2D) gel electrophoresis has been used to identify novel allergens, evaluate changes in levels of expressed protein in response to amphotericin B, as well as build a reference map of different compartments of the cell (3,15,16,22,23,26,43). This conventional approach provides a basis for proteomic analysis but it is limited by the number of protein spots that can be resolved as well as the ability to excise, identify, and quantify the proteins (4).…”
mentioning
confidence: 99%
“…has been identified and quantified until now. The mycellial intracellular proteome of the pathogenic fungus A. fumigatus was characterized in two studies; the first one identified 54 proteins (Carberry et al, 2006) by 2D-PAGE and Ettan MALDI-TOF (Amersham Biosciences) and more recently, the second one identified 381 spots representing 334 proteins (Vödisch et al, 2009) using the same approach and an Ultraflex MALDI-TOF/TOF (Bruker Daltonics). The majority of those proteins were involved in cellular metabolism, protein synthesis, transport processes and cell cycle.…”
Section: Intracellular Reference Mapsmentioning
confidence: 99%